The Influence of Cooperative Learning Models Scramble Types on Student Learning Outcomes on Thematic Learning in Primary Schools - Ginting, Trysia Fiona Br; Mahulae, Saut; Tanjung, Darinda Sofia; Sipayung, Regina; HS, Dyan Wulan Sari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
This research aims to determine the effect of the scramble type cooperative learning model on student learning outcomes on the theme Caring for Animals and Plants class II SDN 040515 Tiga Meeta for the 2023/2024 Academic Year. The research method used is an experimental method with a quantitative research type. To obtain the required data, a test instrument of 32 questions is required. The total research sample was 30 students. To determine students' initial abilities, researchers conducted a PreTest with an average score of 59.3 which fell into the category of not meeting the specified KKM. The results of the PostTest have improved from the PreTest results given previously with the average student score reaching 80 in the good category. It can be said that the level of success in student learning outcomes has increased as evidenced by the results of the correlation coefficient test calculation, which obtained rcount≥rtable results with results of 0.799≥0.361. The value obtained tcount>ttable (7.021> 1.697). So it can be concluded that there is a positive and significant influence between the scramble type cooperative learning model on student learning outcomes.